2006
DOI: 10.5194/angeo-24-1029-2006
|View full text |Cite
|
Sign up to set email alerts
|

A model of the plasma flow and current in Saturn's polar ionosphere under conditions of strong Dungey cycle driving

Abstract: Abstract.We propose a simple model of the flow and currents in Saturn's polar ionosphere. This model is motivated by theoretical reasoning, and guided quantitatively by in situ field and flow data from space missions, ground-based IR Doppler measurements, and Hubble Space Telescope images. The flow pattern consists of components which represent (1) plasma sub-corotation in the middle magnetosphere region resulting from plasma pick-up and radial transport from internal sources; (2) the Vasyliunas-cycle of inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2
2

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 53 publications
(107 reference statements)
2
21
0
Order By: Relevance
“…Very narrow arcs at this boundary, such as that shown in Fig. 1c, may then correspond simply to a region of upwarddirected field-aligned current, as, for example, in the theoretical model of Jackman and Cowley (2006). However, it seems reasonable to suppose that broader features, such as those seen e.g.…”
Section: Summary and Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Very narrow arcs at this boundary, such as that shown in Fig. 1c, may then correspond simply to a region of upwarddirected field-aligned current, as, for example, in the theoretical model of Jackman and Cowley (2006). However, it seems reasonable to suppose that broader features, such as those seen e.g.…”
Section: Summary and Discussionmentioning
confidence: 77%
“…In this case we expect the auroras at Saturn to be associated with Dungey-cycle and possibly Vasyliunas-cycle dynamics, thus also explaining the persistent dawn-dusk local time asymmetries which are observed, as can be seen in Fig. 1 (Cowley et al, 2004aJackman and Cowley, 2006).…”
Section: Summary and Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The second possibility is the flow shear expected to occur at the boundary between closed field lines that moderately sub-corotate, and open field lines in the polar region that strongly sub-corotate according to both theory and observation (Isbell et al, 1984;Stallard et al, 2003Stallard et al, , 2004. Cowley et al (2004a) thus suggested that Saturn's main oval maps to this upward current layer at the boundary between open and closed field lines, a suggestion shown in subsequent modelling to be plausible in terms of accelerated electron and auroral parameters (Cowley et al, 2004b;Jackman and Cowley, 2006). Similar processes may also occur at Jupiter, forming a component of the auroras lying poleward of the main oval .…”
Section: Introductionmentioning
confidence: 88%
“…Gérard et al, 2004;Clarke et al, 2005;Grodent et al, 2005;Badman et al, 2005). The observed auroral emissions relate both to precipitation from hot plasma populations produced within the magnetosphere, and to intense structured field-aligned current systems that are associated with magnetosphere-ionosphere momentum transfer (Cowley et al, 2004a(Cowley et al, , b, 2005aGustin et al, 2004Gustin et al, , 2006Nichols and Cowley, 2004;Jackman and Cowley, 2006).…”
Section: Introductionmentioning
confidence: 99%